Pengembangan media pembelajaran vidsi (video animasi) dengan vlognow untuk pembelajaran PAI mengenai kepemimpinan abu bakar ash-shidiq di SD kelas VI - Dechika Nuhasetia H; Rizka Agustina; Syifa Khoerunnisa; Ani Nuraeni (ARKA INSTITUTE, 2022)
Been doing research on PAI's animated media development on the material of leadership material ash-shidiq with an application Vlognow. The goal of research is to describe the development of the media of learning and media tests are based on the response of teachers, the teachers' response, impact, as well as obstacles. Kind of quality research with a footage of research covering the stage of preliminary studies, the libraka studies, the field survey, and the draft product drafts, as well the development phase with limited trials. This research target is a student of VI Manager's class. The result of this research of the pro-educated interest responders of the media is well reviewed from the components formatic, quality, clarity, as well as the interest of the educated. The media has impact on the competitors the education of studying PAI, understanding of concept, and the arousal of the study and the pleasure of learning, and the interest of learning not only by method of speech as well as they're looking more attractive and not boring. Where the response of SDN Manangga students held, as many as 1 student stated the animated video was not understood, 17 students understood the video and 15 students expressed very understanding the animated video about the leadership of Abu Bakar Ash-Shidiq can be concluded that the animated video based. Vlognow application on Abu Bakar Ash-sidiq leadership material can improve motivation and learning achievements and is considered more understandable and fun and worthy used in the learning process.